La política exterior del gobierno Kiesinger-Brandt - End, Heinrich (Estudios Internacionales, 1968)
Since the formation of the "Grand Coalition" government under Federal Chancellor Kiesinger and Foreign Minister Brandt in December 1966, there has been talk of a new era in German foreign policy. The main lines of the foreign policy of the government of the Great Coalition are contained in the official declaration that Chancellor Kiesinger made before the Bundestag on December 13, 1966. The foreign policy thus outline had to be carried out or at least started before the end of the legislative period in 1966. 18 months since then, it seems legitimate to undertake a critical examination aimed at comparing the practical results obtained so far with the program announced at the beginning of the government period.